Complaint Handling Management at St. Rafael Cancar General Hospital - Lubis, Debi Christian; Nuryakin, Nuryakin; Kusumo, Mahendro Prasetyo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Hospital patients can respond to meet the expectations and realities of the health service they received. If it does not meet their expectations, there will be dissatisfaction. Consumer dissatisfaction is conveyed in the form of criticism and complaints, so good complaint management is required to provide an early warning system to anticipate serious safety incidents resulting in patient dissatisfaction. This includes complaints at St. Rafael Cancar General Hospital, Manggarai, East Nusa Tenggara, where most patients complained about the completeness of inpatient and outpatient services, resulting in a review of the Management of Complaint Handling in Health Services at St. Rafael Cancar General Hospital. This research was conducted on internal management and external patients at St. Rafael Cancar General Hospital, Manggarai, East Nusa Tenggara using qualitative descriptive method with observation and interview with public relations division and patients who have been treated at St. Rafael Cancar General Hospital. The results showed that the management of complaint handling at St. Rafael Cancar General Hospital has not implemented a tiered line of responsibility for complaints. The Public Relations Department often has a role as a complaint resolution party, even though its main function is as a mediator between customers and related units in the management of complaint handling at St. Rafael Cancar General Hospital. Supervision and documentation of complaints at St. Rafael Cancar General Hospital has not developed a Hospital Complaint Management Information System for the effectiveness of complaint resolution control. Patient evaluations showed that they were quite satisfied with the service and follow up on the complaints they have submitted, but there were some service facilities that they think still lacking.